Impact of two Erwinia sp. on the response of diverse Pisum sativum genotypes under salt stress - Ilahi, Houda; Zampieri, Elisa; Sbrana, Cristiana; Brescia, Francesca; Giovannini, Luca; Mahmoudi, Roghayyeh; Gohari, Gholamreza; El Idrissi, Mustapha Missbah; Alfeddy, Mohamed Najib; Schillaci, Martino; Ouahmane, Lahcen; Calvo, Alice; et al. (My University, 2024)
Currently, salinization is impacting more than 50% of arable land, posing a significant challenge to agriculture globally. Salt causes osmotic and ionic stress, determining cell dehydration, ion homeostasis, and metabolic process alteration, thus negatively influencing plant development. A promising sustainable approach to improve plant tolerance to salinity is the use of plant growth-promoting bacteria (PGPB). This work aimed to characterize two bacterial strains, that have been isolated from pea root nodules, initially called PG1 and PG2, and assess their impact on growth, physiological, biochemical, and molecular parameters in three pea genotypes (Merveille de Kelvedon, Lincoln, Meraviglia d'Italia) under salinity. Bacterial strains were molecularly identified, and characterized by in vitro assays to evaluate the plant growth promoting abilities. Both strains were identified as Erwinia sp., demonstrating in vitro biosynthesis of IAA, ACC deaminase activity, as well as the capacity to grow in presence of NaCl and PEG. Considering the inoculation of plants, pea biometric parameters were unaffected by the presence of the bacteria, independently by the considered genotype. Conversely, the three pea genotypes differed in the regulation of antioxidant genes coding for catalase (PsCAT) and superoxide dismutase (PsSOD). The highest proline levels (212.88 μmol g-1) were detected in salt-stressed Lincoln plants inoculated with PG1, along with the up-regulation of PsSOD and PsCAT. Conversely, PG2 inoculation resulted in the lowest proline levels that were observed in Lincoln and Meraviglia d'Italia (35.39 and 23.67 μmol g-1, respectively). Overall, this study highlights the potential of these two strains as beneficial plant growth-promoting bacteria in saline environments, showing that their inoculation modulates responses in pea plants, affecting antioxidant gene expression and proline accumulation.
Keywords: 16S rRNA/DNA; Abiotic stress; Biochemical markers; Pea; RT-qPCR